Traffic and Granular Flow ’03
DOI: 10.1007/3-540-28091-x_36
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization in Pedestrian Flow

Abstract: Microscopic simulation models predict different forms of selforganization in pedestrian flows, such as the dynamic formation of lanes in bi-directional pedestrian flows. The experimental research presented in this paper provides more insight into these dynamic phenomena as well as exposing other forms of self-organization, i.e. in case of over-saturated bottlenecks or crossing pedestrian flows. The resulting structures resemble states occurring in granular matter and solids, including their imperfections (so-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
2

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 7 publications
5
70
2
Order By: Relevance
“…A possible approach was given by Yamori [45] who introduced a band index which is basically the ratio of moving pedestrians in lanes to their total number. Other attempts for lane detection were made by means of the velocity profile [20] and cluster analysis [12]. Here we will use the same order parameter which has been already used in [8] to detect lanes in a colloidal suspension.…”
Section: B Order Parameter For Lane Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible approach was given by Yamori [45] who introduced a band index which is basically the ratio of moving pedestrians in lanes to their total number. Other attempts for lane detection were made by means of the velocity profile [20] and cluster analysis [12]. Here we will use the same order parameter which has been already used in [8] to detect lanes in a colloidal suspension.…”
Section: B Order Parameter For Lane Formationmentioning
confidence: 99%
“…Nevertheless, the phenomenon is best known in pedestrian counterflow from everyday experience although experimental or empirical studies are quite rare [11][12][13][14][15]. The effect can be understood as a self-organization process, where pedestrians try to minimize the contact with other pedestrians, especially if they have a different desired walking direction.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies focused on specific bidirectional characteristics such as lane numbers and selection probabilities [11][12]. The conventional studies, however, mostly targeted normal open-space facilities, such as intersection crosswalks or pedestrian sidewalks, and lacked a qualitative analysis in lane formed and control managements.…”
Section: Establishing Experiments Scenementioning
confidence: 99%
“…Helbing [45] analysed the characteristics of lane and proposed that the number of formed lanes depended on the density in the walking area. Hoogendoorn and Daamen [11] studied it quantitatively by cluster analysis and discovered patterns of two, three, and four lanes. Kretz et al [21] found that an odd number of lanes was likely to break the symmetry.…”
Section: Parameter Definitionmentioning
confidence: 99%
See 1 more Smart Citation